Interventional Treatment of Abdominal Compartment Syndrome during Severe Acute Pancreatitis: Current Status and Historical Perspective - Dejan V. Radenkovic; Colin D. Johnson; Natasa Milic; Pavle Gregoric; Nenad Ivancevic; Mihailo Bezmarevic; Dragoljub Bilanovic; Vladimir Cijan; Andrija Antic; Djordje Bajec (Gastroenterology Research and Practice)
Abdominal compartment syndrome (ACS) in patients with severe acute pancreatitis (SAP) is a marker of severe disease. It occurs as combination of inflammation of retroperitoneum, visceral edema, ascites, acute peripancreatic fluid collections, paralytic ileus, and aggressive fluid resuscitation. The frequency of ACS in SAP may be rising due to more aggressive fluid resuscitation, a trend towards conservative treatment, and attempts to use a minimally invasive approach. There remains uncertainty about the most appropriate surgical technique for the treatment of ACS in SAP. Some unresolved questions remain including medical treatment, indications, timing, and interventional techniques. This review will focus on interventional treatment of this serious condition. First line therapy is conservative treatment aiming to decrease IAP and to restore organ dysfunction. If nonoperative measures are not effective, early abdominal decompression is mandatory. Midline laparostomy seems to be method of choice. Since it carries significant morbidity we need randomized studies to establish firm advantages over other described techniques. After ACS resolves efforts should be made to achieve early primary fascia closure. Additional data are necessary to resolve uncertainties regarding ideal timing and indication for operative treatment.